Exploring the mediating role of students’ satisfaction towards personal record building in the influence of self-regulated learning strategies on employability skills / Sarah Nadiah Rashidi, Faizah Abd Majid and Hamimah Hashim - Rashidi, Sarah Nadiah; Abd Majid, Faizah; Hashim, Hamimah (Universiti Teknologi MARA, 2023)
The issue of employability skills has always been the agenda of stakeholders like the government, universities, and employers in the industry. Dynamic changes to the employability skills needed at workplace require stakeholders to find ways to stay relevant. As an approach to develop desired employability skills, the Personal Record Building (PRB) system was introduced by a technical university. Like ePortfolio, the PRB system mainly relies on students’ ability to self-regulate and record their participation and accomplishment in students’ activities through a merit system. Therefore, it is crucial to explore the relationship between students’ satisfaction towards the PRB, self-regulated learning strategies and employability skills. The objectives of this study are to investigate the influence of self-regulated learning strategies like goal setting, help-seeking and self-monitoring on employability skills and to examine the role of students’ satisfaction towards PRB as a mediator in the relationship between self-regulated learning strategies and employability skills. This study collected data from 159 final year students at a selected technical university through a quantitative method. The data was analysed using SmartPLS structural model assessment. It was discovered that goal setting, self-monitoring and help-seeking strategies significantly influence employability skills. However, students’ satisfaction towards PRB system only mediates the relationship between help-seeking strategies and employability skill. The findings could help universities to assess and improve their services and the PRB system, which would benefit students in developing their self-regulated learning strategies and consequently, their employability skills.